PERBANDINGAN KEPUASAN PASIEN PESERTA JKN DAN NON JKN TERHADAP PELAYANAN RAWAT INAP DI RUMAH SAKIT UMUM PRIMA MEDIKA TAHUN 2020 - Suryaningrat, Anak Agung Sagung Istri Maradi; Indrayathi, Putu Ayu (ARCHIVE OF COMMUNITY HEALTH, 2022)
The Public Relations Satisfaction Survey of Prima Medika Hospital (RSPM) states that an inpatient feels a difference in hospital staff services when he comes for treatment using the Jaminan Kesehatan Nasional (JKN). This study aims to determine differences in patient satisfaction with inpatient services between JKN and non-JKN patients at the RSPM by using quantitative research methods and case survey data collection methods. The sample survey was conducted in a cross-sectional manner with 96 patient respondents consisting of 48 JKN respondents and 48 non-JKN respondents. The satisfaction questionnaire data includes the dimensions of reliability, responsiveness, competence, accessibility, communication, ethics, credibility, security and completeness. Data were analyzed by univariate and bivariate, then hypothesis testing was carried out with the Mann Whitney U. The mean score of JKN patient satisfaction was 3.29 (quite satisfied) and non-JKN patients 3.73 (quite satisfied). The results of the Mann-Whitney statistical test showed a significant difference in satisfaction (p = 5.0704E-10) between JKN and non-JKN respondents. Significant differences were found in doctor's visite service (p = 2.3144E-7), suitability of prescription drugs (p = 7.0098E-11), ease of obtaining inpatient rooms (p = 9.5274E-15) and information on room availability (p = 4.3919E -13). In general, there are differences in satisfaction, where JKN patient satisfaction average is lower than non-JKN patients. Keywords: Satisfaction, JKN, Non JKN, Hospital